High-efficiency solution-processed CdTe nanocrystal solar cells incorporating a novel crosslinkable conjugated polymer as the hole transport layer. (April 2018) - Guo, Xiuzhen; Tan, Qiongxuan; Liu, Songwei; Qin, Donghuan; Mo, Yueqi; Hou, Lintao; Liu, Alei; Wu, Hongbin; Ma, Yuguang
Abstract: Solution-processed nanocrystal (NC) solar cell are attracting much attention for prospective application in low cost energy source; however, the worse collection of hole carriers at the hole interface limits the device performance further improvement. Here, a novel crosslinkable conjugated polymer poly(diphenylsilane- co -4-vinyl-triphenylamine) (Si-TPA) has been applied as the hole transport layer (HTL) for solution-processed CdTe nanocrystal (NC) solar cells. To the best of our knowledge, it is the first report with a crosslinkable conjugated polymer as the HTL in NC solar cells. It is found that the devices with Si-TPA HTL show much better performance than that of the devices without the HTL or with other polymer HTLs such as poly(9-vinylcarbazole) (PVK) and poly(3, 4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS). The improvement with incorporating Si-TPA is attributed to the better energy level matching between the NC film and the Au anode with a good ohmic contact among each interface. Interestingly, it is also observed that introducing Si-TPA can produce a higher open-circuit voltage compared to that without Si-TPA, originating from the interface dipole effect produced by Si-TPA. The improved fill factor value illustrates that the hole and electron carriers are more balanced in the devices with Si-TPA. The champion solar cell with a configuration of ITO/ZnO/CdSe/CdTe/Si-TPA/Au shows a PCE of 8.34%, which is a record for solution-processed CdTe NC solar cells to date with an inverted device structure. Furthermore, for another type of the solution-processed CdS NC device, a high PCE of 7.27% is also obtained with incorporating crosslinkable Si-TPA HTL, which is two times higher than that without Si-TPA, demonstrating the remarkable universality through this method. This work provides a new facile strategy in further increasing solution-processed NC solar cells performance by incorporating organic crosslinkable conjugated polymers as the HTL. Graphical abstract: A novel crosslinkable conjugated polymer poly(diphenylsilane- co -4-vinyl-triphenylamine) (Si-TPA) has been applied as the hole transport layer (HTL) for solution-processed CdTe nanocrystal solar cells and as high as 8.34% power conversion efficiency is obtained in the device.fx1